(untitled) (Actualizaciones en Sida e Infectología, 2023)
Secondary peritonitis is a frequent cause of hospital admission and an usual cause of use of antibiotic therapy in abdominal infections. We did a retrospective and observational study in one health center between January 2021 and December 2021. The aim of the study was to analyze the local epidemiology and adapt antibiotic empirical therapy of secondary community peritonitis. Patients aged 16 years and older with secondary peritonitis were included in this study. These patients needed surgical intervention and they had a positive culture with aerobic microorganism. We analyzed abdominal cultures from 36 patients, 64% men with a median age of 48.8 years. Twenty- two percent of these patients were admitted to intensive care unit. Acute appendicitis was the principal cause of secondary peritonitis in 61% of cases, followed by tumors. We found 43 aerobic bacterias (1.2 bacteria/episode), E.coli was the most frequent microorganism. In our hospital we use piperacillin- tazobactam for empirical treatment. According to the 2018 recommendations from the Argentine Society of Infectious Diseases, aminoglycosides + metronidazole can be used for uncomplicated intra-abdominal infections, and piperacillin-tazobactam should be used only in severe cases. However, ampicillin-sulbactam or ciprofloxacin is not recommended for severe cases or complicated infections due to the high resistance rates. Based on the finding of the study, it could be said that the epidemiology of the patients coincides with what was described in other national medical journals. Therefore, we should reconsider the use of aminoglycosides + metronidazole as empirical treatment for mild cases.